Health Alert Network - Dheeraj Sharma; Ansuman Panigrahi (Archives of Community Medicine and Public Health - Peertechz Publications, 2020)
"Always plan ahead. It wasn't raining when Noah built the Ark." Having said that quote from Richard Cardinal Cushing about emergency preparation, let us move on to our topic "Health Alert Network".